2019
DOI: 10.3389/fimmu.2019.02088
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Blockade Attenuates Thrombosis in a Neutrophil Extracellular Trap-Dependent Breast Cancer Model

Abstract: Cancer patients are at increased risk of developing thrombosis, comorbidity that has been associated with increased neutrophil counts and the formation of neutrophil extracellular traps (NETs). Interleukin-1β (IL-1β) modulates the expression of granulocyte colony-stimulating factor (G-CSF), a cytokine that promotes cancer-associated neutrophilia and NET generation. Herein, we combined a murine breast cancer model with a flow-restriction thrombosis model to evaluate whether the IL-1β blockade could interfere wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 51 publications
(78 reference statements)
1
61
1
1
Order By: Relevance
“…Data were presented as means ± SEM "second-hit" such as infection or stress. Some studies have indicated that NET-promoting effect is attributed to certain tumor-released cytokines or vesicles [30,31]. However, the pattern of secreted factors is highly distinct among various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Data were presented as means ± SEM "second-hit" such as infection or stress. Some studies have indicated that NET-promoting effect is attributed to certain tumor-released cytokines or vesicles [30,31]. However, the pattern of secreted factors is highly distinct among various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Similar antimetastatic effects have been observed in hepatocellular carcinoma and breast cancer models [ 20 , 23 ]. Moreover, the degradation of NETs substantially reduces cancer-associated thrombosis in neutrophilia-related breast and pancreas cancer models [ 26 , 66 ]. Interestingly, we observed that the digestion of NETs with DNase had a minor impact on tumor cell migration as well as in the CXCL8 and MMP9 gene expression ( Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primarily described as an antimicrobial mechanism, NETs are composed of a double-stranded DNA decorated with neutrophil nuclear and granular proteins, such as citrullinated histones, myeloperoxidase, metalloproteinases, and elastase [ 18 ]. Subsequent studies have demonstrated that NETs have several pro-tumoral capabilities, including the ability to sequester circulating tumor cells and contribute to metastasis [ 19 , 20 ], to support primary tumor growth [ 21 , 22 ], to modulate the pro-inflammatory tumor microenvironment [ 23 , 24 ] and to establish the cancer-associated prothrombotic state [ 25 , 26 , 27 ]. It is unclear, however, whether NETs may influence EMT to support tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has recently been shown that immature neutrophils preferentially respond to cancer cell derived C3a to promote their migration (31). Subsequently, it was shown that breast cancer cells that expressed high levels of G-CSF and IL-1β exhibited high neutrophil counts and tumor-associated thrombosis, which was dependent on NET formation (32). Pharmacological blockade of IL-1 receptor signaling reduced NET formation, attenuated tumor-associated thrombosis and impaired tumor growth (32).…”
Section: Neutrophil Functions That Promote Primary Tumor Growthmentioning
confidence: 99%
“…Subsequently, it was shown that breast cancer cells that expressed high levels of G-CSF and IL-1β exhibited high neutrophil counts and tumor-associated thrombosis, which was dependent on NET formation (32). Pharmacological blockade of IL-1 receptor signaling reduced NET formation, attenuated tumor-associated thrombosis and impaired tumor growth (32). NETs can also directly influence cancer cell proliferation.…”
Section: Neutrophil Functions That Promote Primary Tumor Growthmentioning
confidence: 99%